Multilevel Genome Typing Describes Short- and Long-Term Vibrio cholerae Molecular Epidemiology - Liam Cheney (American Society for Microbiology, 2021)
In 2017, the World Health Organization launched the “Ending Cholera” initiative to reduce cholera-related deaths by 90% by 2030. This strategy emphasized the importance of the speed and accessibility of newer technologies to contain outbreaks.